The Effect of Chemical Composition of Materials on the Values of Engineering Stresses Emerging in Metal Connections with Fire - فايز نصره مهند (Latakia University Journal -Engineering Sciences Series, 2020)
In this research, the finite element theory has been applied to orthogonal joints consisting of a permissible and a column that were linked together by bolts and nuts, by relying on three-dimensional design programs, the most important of which was CATIA V5 in order to know the behavior of this type of joints at elevated temperatures in the event of fire or Heat source. This type of joint was chosen because it is used extensively in most metal installations. This research focuses on understanding the effect of the properties of materials from which the nerve and the plate can be chosen on the behavior of the connections used with increasing temperatures and determines the breakdown of each joint at each type of material proposed in this research. The materials were chosen from different mixtures and entered to the program interface accurately in order to calculate the resulting stresses in the link at each case accompanying each temperature starting from the ambient temperature of 20 ° C to 1600 ° C and all cases were compared with each other to know the differences in stress values Emerging and determining which materials have withstood and endured more, after installing all other parameters of the link so that the understanding of the effect of the plate and the nerve becomes clearer on the stress values. The IPE 240 studied connection is made up of eight screws with a diameter of 22 mm and a thickness of a plate of 15mm, with the presence of a reinforcement nerve with a thickness of 30mm and an angle of inclination of 50 °.